Cosolvent selection for supercritical fluid extraction (SFE) of bioactive compounds from Orthosiphon stamineus - Masniza Mohamed@Mahmood,; Wan Ramli Wan Daud,; Masturah Markom,; Che Nurul Ain Nadirah Che Mansor, (Penerbit Universiti Kebangsaan Malaysia, 2018)
In this work, a preliminary study was conducted to study the effects of different types and concentrations of cosolvents based on the total yield and antioxidants capacity prior to supercritical fluid extraction (SFE) of Orthosiphon stamineus (locally referred as misai kucing). Initially, a comparison was made by cold maceration technique with nine types of different cosolvents, namely water, pure ethanol, 25% (v/v) of ethanol in water, 50% (v/v) of ethanol in water, 75% (v/v) of ethanol in water, pure methanol, 25% (v/v) of methanol in water, 50% (v/v) of methanol in water and 75% (v/v) of methanol in water. The antioxidant capacity was analysed by free radical scavenging activity of 2,2-diphenyl-1-picrylhydrazyl (DPPH), total phenolic content (TPC) and total flavonoid content (TFC). Aqueous ethanolic solvent of 50% (v/v) ethanol in water showed the highest total yield of extract of 4.64 ± 0.02%. All antioxidant assays of TPC and TFC showed the highest value of 3.42 ± 0.08 mg GAE g−1 extract, 4.7 ± 0.14 mg CAE g−1 extract, respectively and IC50 value for DPPH was 0.625 μg/mL for 50% (v/v) ethanol in water extract. Based on the overall result, ethanolic solvents gave a better result for all antioxidant assays compared to those of methanolic solvents. Using the selected cosolvent, the identification of target compounds, which were rosmarinic acid, eupatorin and sinensetin from supercritical fluid extraction was determined by using HPLC. In conclusion, ethanol-water solvent was efficient in extracting bioactive compounds in O. stamineus and also improved the total yield, thus the usage of ethanolic solvent in different concentrations should be considered for further optimisation of SFE with cosolvent studies.